2022
DOI: 10.1021/acsomega.1c07282
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Energetic Performance of CL-20 by Surface Modification Using Tannic Acid and Energetic Coordination Polymers

Abstract: The energetic performance of hexanitrohexaazaisowurtzitane (CL-20) was modulated with two energetic coordination polymers (ECPs), [Cu(ANQ) 2 (NO 3 ) 2 ] and [Ni(CHZ) 3 ](ClO 4 ) 2 , in this study by a two-step method. First, tannic acid polymerized in situ on the surface of CL-20 crystals. Then, [Cu(ANQ) 2 (NO 3 ) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The gradual weakening or disappearance of diffraction peaks as particle granularity decreases is a well-known phenomenon. For instance, characteristic peaks of CL-20, typically observed at 12.6 • , 13.8 • , and 25.8 • according to the literature [15], closely align with the data presented in Table 2. Notably, the full width at half maximum (FWHM) values of CL-20/NC are higher than those of CL-20, with some even approximately tripling.…”
Section: Dsc Analysissupporting
confidence: 86%
“…The gradual weakening or disappearance of diffraction peaks as particle granularity decreases is a well-known phenomenon. For instance, characteristic peaks of CL-20, typically observed at 12.6 • , 13.8 • , and 25.8 • according to the literature [15], closely align with the data presented in Table 2. Notably, the full width at half maximum (FWHM) values of CL-20/NC are higher than those of CL-20, with some even approximately tripling.…”
Section: Dsc Analysissupporting
confidence: 86%
“…Yuan and co-workers designed a high-energy explosive CL-20 with double-layer coating structure modification (Figure ). With tannic acid as the intermediate layer, the double-layer core–shell energy materials CL-20/TA/[Cu­(ANQ) 2 (NO 3 ) 2 ] and CL-20/TA/[Ni­(CHZ) 3 ]­(ClO 4 ) 2 were prepared with two high-energy metal complexes [Cu­(ANQ) 2 (NO 3 ) 2 ] and [Ni­(CHZ) 3 ]­(ClO 4 ) 2 as the shell. Through performance testing and calculation, compared with uncoated CL-20, the impact sensitivity of CL-20 was reduced by 58% and the energy was reduced by 2.5%, which achieved the purpose of reducing the sensitivity of CL-20 while maintaining high energy.…”
Section: Application Of Biological Polyphenol In Energetic Materialsmentioning
confidence: 98%
“…Yuan and co-workers designed a high-energy explosive CL-20 with double-layer coating structure modification (Figure 9). 72 With tannic acid as the intermediate layer, the double- by 58% and the energy was reduced by 2.5%, which achieved the purpose of reducing the sensitivity of CL-20 while maintaining high energy.…”
Section: Preparation Of Biomass Polyphenolmentioning
confidence: 99%
“…6–12 Among them, energetic complexes (ECs) based on the coordination self-assembly of metal ions and nitrogen-rich ligands have the advantages of a high energy level, a large specific surface area and high gas production, thus receiving widespread attention in the field of energetic materials and combustion promoters. 9,13–21…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Among them, energetic complexes (ECs) based on the coordination selfassembly of metal ions and nitrogen-rich ligands have the advantages of a high energy level, a large specific surface area and high gas production, thus receiving widespread attention in the field of energetic materials and combustion promoters. 9,[13][14][15][16][17][18][19][20][21] In the process of research, however, ECs gradually showed the shortcomings of poor conductivity, thermal conductivity and safety performance. In addition, carbon nanomaterials have a large surface area and excellent conductivity, but they are inert and easy to aggregate.…”
Section: Introductionmentioning
confidence: 99%